KUALITAS PELAYANAN RECEPTIONIST DI ANGSANA RESORT AND SPA BINTAN - Mhd. Norkairisah; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Angsana Resort and SPA Bintan is one of the premium resorts under of the Banyan Tree Holding Limited. Angsana Resort and SPA Bintan has the most complaints among other resorts under Banyan Tree ownership. This is caused by service quality of Receptionist that have not been perfectly implemented in the Front Office especially. This research was conducted to find out whether the service quality of receptionist provided has been carried out properly or not. This research uses quantitative research methods descriptive approach. Data obtained from the results of filling out the questionnaire that has been given to guests who have stayed at Angsana Resort and SPA Bintan and interviews. The samples in this study were 100 people taken from accidental sampling technique. The measurement technique used in this research questionnaire is a Likert scale, then the data will be processed into numerical data aimed at getting results to be drawn conclusions. Keyword : Angsana Resort and SPA, Receptionist, Service Quality